Determination of the critical period of weed control in corn using a thermal basis - Bedmar, Francisco; Manetti, Pablo; Monterubbianesi, Gloria (Pesquisa Agropecuaria Brasileira, 1999)
Field studies were conducted over 3 years in southeast Buenos Aires, Argentina, to determine the critical period of weed control in maize (Zea mays L.). The treatments consisted of two different periods of weed interference, a critical weed-free period, and a critical time of weed removal. The Gompertz and logistic equations were fitted to relative yields representing the critical weed-free and the critical time of weed removal, respectively. Accumulated thermal units were used to describe each period of weed-free or weed removal. The critical weed-free period and the critical time of weed removal ranged from 222 to 416 and 128 to 261 accumulated thermal units respectively, to prevent yield losses of 2.5%. Weed biomass proved to be inverse to the crop yield for all the years studied. When weeds competed with the crop from emergence, a large increase in weed biomass was achieved 10 days after crop emergence. However, few weed seedlings emerged and prospered after the 5-6 leaf maize stage (10-20 days after emergence).